Identifying fiscal policy (in)effectiveness from the differential adoption of Keynesianism in the interwar period - Nicolas-Guillaume Martineau; Gregor W. Smith (Queen's University, Department of Economics, 2012)
Differences across countries or decades in the countercyclical stance of fiscal policy can help identify whether the growth in government spending affects output growth and so speeds recovery from a recession. We use the heterogeneity in the government-spending reaction functions across twenty countries in the interwar period to identify this effect. The main finding is that the growth of government spending did not have a significant effect on output growth, so that there is little evidence that this central aspect of fiscal policy played a stabilizing role from 1920 to 1939.
Keywords: E32; E65; N10; 330; fiscal policy; business-cycle history; Great Depression; interwar economy